GARBRAND HALL (1674)
Diagram represents separate parcels of land in and around Garbrand Hall for the persons listed, including two for John Garbrand and one for Caleb Garbrand located in the parish of St. Thomas.
Estate Map
NLJCols20082021
Keywords: Negro River; Morant River; GARBRAND HALL